Prime Minister's Decree No. 4666 of the year 2022 Amending Certain Provisions of the Executive Regulations of the Law Regulating Movable Guarantees Promulgated By Minister of Investment Decree No. 108 of the Year 2016 = قرار رئيس مجلس الوزراء رقم 4666 لسنة 2022 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم الضمانات المنقولة الصادرة بقرار وزير الاستثمار رقم 108 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic